The role of the public sector in developing tourism product strategies for tourism destinations - Gołembski, Grzegorz (Economics and Business Review, 2004)
Tourism product is an amalgam of goods and services purchased by tourists at their place of residence, while travelling, and at their target destination. A tourism destination is where the bulk of tourism and hospitality businesses are based, entities whose work determines perceptions of the tourism product quality. The quality of an overall offering depends on the quality of the package design and its agreement with customer expectations. In the areas where tourism potential (natural and anthropogenic values) is not utilised, the prime issue is the quality of the design, and that calls for a tourism strategy development. The paper attempts to justify the thesis that the prime role in this strategy development is played by public sector entities, both at the stage of identifying tourism destinations and their products, and in the process of developing those products. (original abstract)